Eksistensi Telok Abang Sebagai Tradisi Agustusan Di Kota Palembang Tahun 2010-2020 - Syarifuddin; Irene Maria Virgina Pratama Sipayung; Magraini (Universitas Pendidikan Ganesha, 2022)
Telok Abang is one of the characteristics of the city of Palembang in welcoming the commemoration of the Independence Day of the Republic of Indonesia. Telok Abang is a red boiled egg which is usually plugged into a boat, the toy cars are made of wood or cardboard. Telok brother is used as a symbol against the Dutch colonialists. The red color shows resistance and struggle against colonialism, while the egg is a symbol of life. This article discusses several important things related to Telok Abang, namely the history of the Telok Abang celebration in Palembang, the outline of the Telok Abang week. Furthermore, this article provides an interpretation of cultural acculturation in the event. This study uses qualitative analysis techniques supported by interviews, namely analysis based on cause-and-effect relationships of historical phenomena in the scope of time and place.